Inhibitory Effect of Sub-conjunctival Tocilizumab on Alkali Burn Induced Corneal Neovascularization in Rats. (January 2015) - Sari, Esin Sogutlu; Yazıcı, Alper; Aksit, Hasan; Yay, Arzu; Sahin, Gözde; Yildiz, Onur; Ermis, Sıtkı Samet; Seyrek, Kamil; Yalcin, Betul
Abstract Background: To evaluate the effects of sub-conjunctivally applied interleukin-6 receptor (IL-6R) antibody (tocilizumab) on alkali burn induced corneal neovascularization (CNV) in rats. Methods: Alkali burn induced corneal neovascularization was created in 24 right eyes of 24 rats. The rats were then randomized into 2 groups. Group 1 received sub-conjunctival injection of 4 mg/0.2 ml tocilizumab and Group 2 received sub-conjunctival injection of 0.2 ml normal saline at the 5th day of alkali burn. The corneal surface area invaded with neovascular vessels were calculated on photographs. The rats were sacrificed and the corneas were excised at the15th day. The corneal specimens were stained with hemotoxylin-eosin to evaluate tissue morphology and with Willebrand factor (vWF) to evaluate microvascular structures immunohistochemically. Vascular endothelial growth factor (VEGF) expression was analyzed by ELISA. Results: The percent area of CNV was 26.9% in Group 1 and 56.5% in Group 2 (p < 0.001). The histological evaluation showed that the corneal structures were not visibly altered by sub-conjuntival tocilizumab injection. Group 1 showed significantly lower corneal inflammation score than Group 2 (p < 0.001). The number of vessels stained with vWF were significantly higher in Group 2 than Group 1 (15.23 and 5.46, respectively; p < 0.001). ELISA analyses showed that corneal VEGF levels were significantly lower in Group 1 compared to Group 2 (p = 0.013) Conclusion: The present data demonstrated first time the beneficial effects of sub-conjunctival tocilizumab on decreasing CNV in alkali burn model of the rat cornea. Further studies are warranted to confirm these findings for the clinical application.